1996
DOI: 10.1046/j.1365-2796.1996.468809000.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking on blood pressure and proteinuria in patients with diabetic nephropathy

Abstract: Smoking increases blood pressure values in healthy subjects and in hypertensive patients with diabetic nephropathy and without autonomic neuropathy. This effect of smoking may be partly responsible for the faster progression of diabetic nephropathy in smoking diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 11 publications
0
17
1
Order By: Relevance
“…In Type I diabetes it has been shown to independently increase the degree of nephropathy [15]. In our study half of the participants smoked an average of 20 cigarettes a day.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In Type I diabetes it has been shown to independently increase the degree of nephropathy [15]. In our study half of the participants smoked an average of 20 cigarettes a day.…”
Section: Discussionmentioning
confidence: 51%
“…Several additional factors like glomerular hyperfiltration [13], high blood pressure [14], smoking [15] and genetic predisposition [16±17] are probably coplayers in the development of diabetic nephropathy but their role in the more short-term development of the specific glomerulopathy is not clear.…”
Section: : 253±261]mentioning
confidence: 99%
“…This was also found in some previous cross-sectional or prospective studies (24,25), but not in all studies (9,18). It has been suggested that smoking induces acute increases in blood pressure (26,27) and increases vascular permeability in nondiabetic subjects, but this was not confirmed in other studies (27).…”
Section: Albumin Progression Ratementioning
confidence: 67%
“…In patients with diabetes mellitus, presence or absence of autonomic neuropathy is a major determinant of the effects of smoking on BP. For instance, among patients with type 1 diabetes, smoking increased systolic BP only in subjects without autonomic neuropathy (80).…”
Section: Potential Mechanisms Of Smoking-induced Renal Damagementioning
confidence: 99%